Thalidomide Combined With Azathioprine as Induction and Maintenance Therapy for Azathioprine-Refractory Crohn's Disease Patients - Li, Tong; Qiu, Yun; Li, Xiaozhi; Zhuang, Xiaojun; Huang, Shanshan; Li, Manying; Feng, Rui; Chen, Baili; He, Yao; Zeng, Zhirong; Chen, Minhu; Zhang, Shenghong (Frontiers in Medicine, 2020)
The combination therapy of thalidomide and azathioprine [AZA] offers an alternative in clinical practice for Crohn’s disease [CD] patients in whom AZA monotherapy had failed. However, little is known about the efficacy and safety of this combination therapy for patients with CD. This was a retrospective study of 122 consecutive CD patients in whom AZA therapy had failed and had switched to a combination therapy of thalidomide and AZA. The primary outcomes were clinical response and clinical remission rates at week 24. Patients who had an initial response to combination therapy were continued on the treatment for remission maintenance. The secondary outcomes were the proportion of clinical relapse throughout maintenance. The Kaplan-Meier method was used to calculate cumulative rates, and Cox regression analysis was used for multivariate analysis. During induction, 80.3% (98/122) patients achieved clinical response within a median duration of 6.5 weeks, (interquartile range, 4.3-8.1 weeks). The rate of clinical remission at 24 weeks was 70.5%. During follow-up, 22.4% (22/98) of the patients that were maintained on combination therapy experienced clinical relapse. The proportions of patients in remission status at 12, 24, and 36 months were 85.1%, 78.3% and 70.1%, respectively. Multivariate analysis revealed C-reactive protein >10 mg/L at AZA failure (adjusted hazard ratio [HR], 4.72; 95% CI, 1.19-18.75, P = 0.027) and 6-thioguanine nucleotides level ≥235 pmol/8 × 108 erythrocytes at AZA monotherapy (adjusted HR, 5.32; 95% CI, 1.40-20.14, P = 0.014) were associated with disease relapse. The endoscopic remission rate was 63.6%. Mucosal healing was achieved in 23.6% of the patients. Both Crohn’s Disease Endoscopic Index of Severity (13.4±4.92 vs. 6.12±5.24, P <0.001) and Rutgeerts scores (3.23±0.73 vs. 1.77±1.59, P = 0.003) were significantly decreased with the use of combination therapy. Adverse events occurred in 62 (50.8%) patients, but only 13 (10.7%) necessitated therapy discontinuation. Thalidomide combined with AZA was effective in inducing clinical remission and sustaining long-term steroid-free remission in CD patients who failed in AZA monotherapy.